2004
DOI: 10.2343/geochemj.38.265
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenic, nucleogenic and fissiogenic noble gas compositions in early Archaean magmatic zircons from Greenland

Abstract: We report a full suite of radiogenic, nucleogenic and fissiogenic noble gas compositions obtained by step-heating experiments from early Archaean Greenland zircons. We estimated activation energy (E a ) of diffusion and closure temperatures (T c ) for radiogenic 4 He* and fissiogenic 86 Kr* and 136 Xe* in zircons. These data demonstrate that the combined study of (U-Th)/He and (U-Th)/Kr-Xe can provide powerful geochronological information on cooling ages and crystallization ages from the same samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…They may be applied to other U,Th rich minerals like monazite and zircon as well. In fact, this is also demonstrated from some recent studies of magmatic Archaean zircons from Greenland showing good retention of nucleogenic 21 Ne (Honda et al, 2004).…”
Section: Age Estimation From In Situ 4 He 21 Ne and 136 Xesupporting
confidence: 62%
“…They may be applied to other U,Th rich minerals like monazite and zircon as well. In fact, this is also demonstrated from some recent studies of magmatic Archaean zircons from Greenland showing good retention of nucleogenic 21 Ne (Honda et al, 2004).…”
Section: Age Estimation From In Situ 4 He 21 Ne and 136 Xesupporting
confidence: 62%
“…Although release temperatures for Ne and Xe in these common minerals are currently uncertain, on the basis of their diffusivity decrease with increasing atomic numbers [ Ozima and Podosek , 2002], it is reasonable to assume that Ne release temperatures will fall between those of He and Ar (e.g., ∼70–250°C), while Xe release temperatures are expected to be greater than those of Ar (e.g., >275°C). These assumptions are supported by the increasing release temperatures for 4 He, 21 Ne, 84 Kr, and 136 Xe in zircons [ Honda et al , 2004; Gautheron et al , 2006], as well as the observed Xe release temperature in meteorites, which was shown to be greater than that of Ar [ Burkland et al , 1995]. Because of its currently low geothermal gradient (∼19°C/km) [ Vugrinovich , 1989], fluid temperatures in most of our sampled formations in the Michigan Basin are ∼40–80°C, far lower than release temperatures required for 40 Ar and 136 Xe.…”
Section: Discussionmentioning
confidence: 92%
“…non-irradiated aliquots of three of the six samples using the VG 5400 noble gas mass spectrometer also at the ANU (Honda et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Analogous noble gas extraction procedures were used for isotopic analysis of He, Ne, Ar, Kr and Xe on the VG 5400 noble gas mass spectrometer. The differences were that the custom built air-actuated crushing devise accommodates larger samples (Matsumoto et al, 2001) (Honda et al, 2004).…”
Section: Methodsmentioning
confidence: 99%